2016
DOI: 10.1016/j.jhep.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of cirrhosis among U.S. adults aware or unaware of their chronic hepatitis C virus infection

Abstract: Background and Aims Cirrhosis from hepatitis C virus (HCV) infection is a major cause of end-stage liver disease and hepatocellular carcinoma worldwide. We determine the prevalence of cirrhosis among HCV-infected American adults including those unaware of their infection. Methods Using the National Health and Nutrition Examination Survey (NHANES) data, we identified participants aged≥20 years with detectable serum HCV RNA. The prevalence of advanced fibrosis and cirrhosis was determined for Eras 1 (1988-94),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 27 publications
3
46
0
Order By: Relevance
“…Noninvasive methods had overcome the limitations of liver biopsy and were also used as prognostic indices for subjects with hepatitis B-associated HCC [39]. Furthermore, the accuracy of FIB-4 and APRI were 78% and 76% [40], suggesting they were suitable for regular monitoring of disease progression [41,42]. Thus, using APRI and FIB-4 to assess liver fibrosis was acceptable in the circumstances of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive methods had overcome the limitations of liver biopsy and were also used as prognostic indices for subjects with hepatitis B-associated HCC [39]. Furthermore, the accuracy of FIB-4 and APRI were 78% and 76% [40], suggesting they were suitable for regular monitoring of disease progression [41,42]. Thus, using APRI and FIB-4 to assess liver fibrosis was acceptable in the circumstances of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a major cause of chronic liver disease, with an estimated infection rate of 185 million individuals globally . The National Health and Nutrition Examination Survey (2003–2010) reported that ~2.7 million US residents had chronic HCV infection . The recent development of direct‐acting antiviral agents (DAAs) has transformed the management of patients with chronic HCV, and treatments are associated with sustained virological response (SVR) rates of >95% .…”
Section: Introductionmentioning
confidence: 99%
“…While the prevalence of HCV infection peaked in the early 2000s and has been decreasing in the US 15, 16 , an increasing proportion of HCV patients have advanced stage liver disease. 17 Therefore, the absolute number of HCV patients who remain at high risk for HCC may have increased. Successful HCV eradication has been shown to be associated with an 81% reduction in the risk of HCC development in HCV patients with advanced fibrosis or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%